2006
DOI: 10.1007/s10800-006-9249-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stannous ions on the electrochemical performance of the alkaline zinc electrode

Abstract: The effect of stannous ions as an electrolyte additive on the electrodeposition characteristics of Zn was investigated by chronoamperometry, the potential-step method and cyclic voltammetry. The chronoamperometry measurements showed that the addition of stannous ions inhibited the dendritic growth of Zn deposits. SEM observation also revealed that the Zn deposit was in the form of compact cylinders with rounded tops that consist of many small crystallites, rather than the classical dendrites with side branches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Extensive demand from a wide spectrum of industrial applications has been the major driving force for research on corrosion resistant materials, leading to the development of chromium-based corrosion resistant alloys such as Cr-Ni, Cr-Fe and Cr-W-Ni [1][2][3][4][5][6]. However, few studies on electrodepositing Fe-Ni-Cr alloy on Fe substrate have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive demand from a wide spectrum of industrial applications has been the major driving force for research on corrosion resistant materials, leading to the development of chromium-based corrosion resistant alloys such as Cr-Ni, Cr-Fe and Cr-W-Ni [1][2][3][4][5][6]. However, few studies on electrodepositing Fe-Ni-Cr alloy on Fe substrate have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chronoamperometry as a tool to evaluate dendrite formation on the zinc surface has been studied widely. Smaller deposition currents when a polished zinc foil are in contact with the gel electrolyte, suggesting that the growth of dendrite on the zinc surface is suppressed. Previous studies suggested that highly uniform zinc deposition is expected at low current density. Furthermore, it has been shown that high mechanical modulus of electrolyte can suppress the dendrites growing on metal electrodes . On the other hand, immobilization of anions leads to a larger transference number of cations that are shown to suppress dendrite growth .…”
Section: Resultsmentioning
confidence: 99%
“…Polymers include polyethyleneimine (Banik and Akolkar, 2015 ; Hashemi et al, 2017 ), Triton X-100 (Kan et al, 1998 ), polyvinyl alcohol (Ortiz-Aparicio et al, 2013 ), polyethylene glycol (Lee et al, 2006a ; Ballesteros et al, 2007 ; Banik and Akolkar, 2013 ), polyacrylamide (Zhang et al, 2019b ), Tween 20 (Chladil et al, 2019 ), and Pluronic F-127 (Hosseini et al, 2018 ). Metal ions comprise Pb 2+ (Justinijanović et al, 1973 ; Wen et al, 2012 ), Sn 2+ (Yuan et al, 2007 ; Kim and Shin, 2015 ; Yao et al, 2019 ), Bi 3+ (Wang et al, 2001 ), In 3+ (Leung et al, 2011 ), and La 3+ (Yang et al, 2004 ).…”
Section: Strategies To Prevent Zinc Dendrite Formationmentioning
confidence: 99%